Fraturas do quadril no idoso: mortalidade e comprometimento da marcha - Moreira, Tiago Amaral Rebouças (2013)
Introduction: Approximately 1.5 million hip fractures ocurr annually worldwide in elderly people, this number is expected to increase to 6.3 million by 2050. Mortality rates within the first year varies from 11.2% to 35%. An estimated 23 – 50% of these patients recover their previous walking ability. Factors involved in the increased mortality of these patients are not completely understood. The objective of the presente study was to evaluate the morbimortality of elderly patients treated surgically for hip fracture. Patients and methods: Medical records of patients ≥60 years of age who underwent surgery for the treatment of hip fracture between 1 January 2010 and 31 December 2011 in a reference hospital of the Central-West region of Brazil were retrospectively analysed. Patients with history of high-energy trauma, pathologic fracture due to bone tumor or unable to walk before the fracture were excluded. The variables under study were: gender, age, comorbidities, previous hip fracture, fracture type, time between admission and surgery, assisted walking before injury, and hospitalization time. The follow-up period was 1 year. Univariate and multivariate (Cox proportional hazards) analyses were performed. The survival curve was estimated by using the Kaplan-Meier method. Results: Of the 835 patients with hip fractures, 427 were included in the study. Of these, 63.5% were women. One hundred and twenty-nine patients died; 38.0% of them were men. Age and length of hospital stay were associated with progression to death (p = 0.000). On Cox analysis, an age ≥ 90 years (hazard ratio [HR], 3.54; 95% confidence interval [CI], 1.46–8.59) and the presence of chronic obstructive pulmonary disease (HR, 2.44; 95%: CI, 1.25–4.74) proved to be predictors of death. Among the survivors, 58.7% exhibited the same walking ability they had before the injury and 14.7% became wheelchair-bound. Conclusions: The mortality rate in the first year was 30.2%. Age ≥90 years and chronic obstructive pulmonary disease were identified as predictors of death. Among those patients who were alive after 1 year, 52.5% maintained the ability to walk without assistance and 14.7% became wheelchair-bound.